The functions of the cytoskeleton and associated proteins during mitosis and cytokinesis in plant cells - Li, Shanwei; Sun, Tiantian; Ren, Haiyun (Frontiers in Plant Science, 2015)
In higher plants, microtubule (MT)-based, and actin filament (AF)-based structures play important roles in mitosis and cytokinesis. Besides the mitotic spindle, the evolution of a band comprising cortical MTs and AFs, namely, the preprophase band (PPB), is evident in plant cells. This band forecasts a specific division plane before the initiation of mitosis. During cytokinesis, another plant-specific cytoskeletal structure called the phragmoplast guides vesicles in the creation of a new cell wall. In addition, a number of cytoskeleton-associated proteins are reportedly involved in the formation and function of the PPB, mitotic spindle, and phragmoplast. This review summarizes current knowledge on the cytoskeleton-associated proteins that mediate the cytoskeletal arrays during mitosis and cytokinesis in plant cells and discusses the interaction between MTs and AFs involved in mitosis and cytokinesis.